Genotoxicity of malachite green and leucomalachite green in female Big Blue B6C3F1 mice - Mittelstaedt, Roberta A.; Mei, Nan; Webb, Peggy J.; Shaddock, Joseph G.; Dobrovolsky, Vasily N.; McGarrity, Lynda J.; Morris, Suzanne M.; Chen, Tao; Beland, Frederick A.; Greenlees, Kevin J.; Heflich, Robert H. (Mutation research, 2004)
Malachite green, a triphenylmethane dye used in aquaculture as an antifungal agent, is rapidly reduced in vivo to leucomalachite green. Previous studies in which female B6C3F1 mice were fed malachite green produced relatively high levels of liver DNA adducts after 28 days, but no significant induction of liver tumors was detected in a 2-year feeding study. Comparable experiments conducted with leucomalachite green resulted in relatively low levels of liver DNA adducts but a dose-responsive induction of liver tumors. In the present study, we fed transgenic female Big Blue B6C3F1 mice with 450 ppm malachite green and 204 and 408 ppm leucomalachite green (the high doses used in the tumor bioassays) and evaluated genotoxicity after 4 and 16 weeks of treatment. Neither malachite green nor leucomalachite green increased the peripheral blood micronucleus frequency or Hprt lymphocyte mutant frequency at either time point; however, the 16-week treatment with 408 ppm leucomalachite green did increase the liver cII mutant frequency. Similar increases in liver cII mutant frequency were not seen in the mice treated for 16 weeks with malachite green or in female Big Blue rats treated with a comparable dose of leucomalachite green for 16 weeks in a previous study [Mutat. Res. 547 (2004) 5]. These results indicate that leucomalachite green is an in vivo mutagen in transgenic female mouse liver and that the mutagenicities of malachite green and leucomalachite green correlate with their tumorigenicities in mice and rats. The lack of increased micronucleus frequencies and lymphocyte Hprt mutants in female mice treated with leucomalachite green suggests that its genotoxicity is targeted to the tissue at risk for tumor induction.